Continuing Professional Development (CPD) Impact to Clinical and Nursing Practice: A systematic literature review - Haeril Amir; Tutik Sri Hariyati; Enie Novieastari (ACHSM, 2024)
Introduction and aims: Professionalism is an obligation for nurses in carrying out nursing care in hospitals and this is obtained from continuing professional development (CPD). The aim of this research is to review the benefits of CPD in nursing practice. Material and methods: This paper is a literature review using several databases, namely Scopus, PubMed, Science Direct. Articles were searched with the keywords /MeSh "[Continuing Professional Development]" OR "[CPD] AND "[Nursing]"AND [Professional]. Result: Based on the search results, 9 articles were found with mixed methods n=2, qualitative n= 2 and quantitative n=5. Conclusion: CPD impacts nurses' knowledge, skills, job retention, patient safety and quality of care.